A decade of change – lessons learned from prenatal diagnostics in Central Denmark region in 2008–2018 - Dorte Launholt Lildballe; Naja Becher; Else Marie Vestergaard; Rikke Christensen; Stina Lou; Puk Sandager; Lars Henning Pedersen; Kasper Gadsbøll; Olav Bjørn Petersen; Ida Vogel (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction In 2011, it was decided to implement chromosomal microarray in prenatal testing in the Central Denmark Region, mainly due to the expected higher diagnostic yield. Chromosomal microarray was introduced gradually for an increasing number of pregnancies and without a transition period where both karyotyping and chromosomal microarray were performed: first malformations (2011), then large nuchal translucency (2013), then high risk at combined first trimester risk screening (2016) and finally for all indications (2018). This retrospective study summarizes 11 years of using chromosomal microarray in invasive prenatal testing and presents the effect on diagnostic yield and turnaround time. Furthermore, the concerns when introducing chromosomal microarray are presented and discussed. Material and methods Registry data from the Danish Fetal Medicine Database, the regional fetal medicine database, the Danish Cytogenetic Central Register and the local laboratory database at Department of Clinical Genetics were all combined, and a cohort of 147 158 singleton pregnancies with at least one ultrasound examination was established Results Of the 147 158 pregnancies, invasive sampling was performed (chorionic villi or amniocytes) in 8456, corresponding to an overall invasive rate of 5.8%. Between 2016 and 2018, 3.4% (95% confidence interval [CI] 2.8–4.2%; n = 86) of the invasive samples (n = 2533) had a disease causing copy number variant and 5.3% (95% CI 4.4–6.2%; n = 133) had trisomies and other aneuploidies. The turnaround time more than halved from 14 days to an average of 5.5 days for chorionic villus sampling. Conclusions Chromosomal microarray identified 5.3% trisomies and 3.4% copy number variants, thereby increased the diagnostic yield by more than 64% compared with karyotype only and it also more than halved the turnaround time. Some preliminary concerns proved real, eg prenatal counseling complexity, but these have been resolved over time in a clinical path with expert consultations.